Reducing the Harms of College Student Drinking: How Alan Marlatt Changed Approaches, Outcomes, and the Field - Kilmer, Jason R. (Addict Res Theory, 2012)
In this article, we discuss Alan Marlatt’s contributions to the prevention and reduction of alcohol-related harms among college students. We consider Alan’s early research that later led to the development and evaluation of college student drinking programs, and examine Alan’s impact, both directly and indirectly through those he mentored and trained, as a scientist-practitioner. We review the recognition of the efficacy of Alan’s programs, including the Alcohol Skills Training Program (ASTP) and Brief Alcohol Screening and Intervention for College Students (BASICS), in addition to extensions of these interventions in more recent studies. Finally, we discuss how Alan’s work influences interventions with college student drinkers today, and how future directions will continue to be informed by his vision and values.